Aboriginal and Torres Strait Islander women's views of cervical screening by self‐collection: a qualitative study. (3rd February 2022) - Whop, Lisa J.; Butler, Tamara L.; Lee, Natasha; Cunningham, Joan; Garvey, Gail; Anderson, Kate; Condon, John R.; Tong, Allison; Moore, Suzanne; Maher, Clare M.; Mein, Jacqueline K.; Warren, Eloise F.; et al.
Abstract: Objective : This study aimed to describe Aboriginal and Torres Strait Islander women's views of self‐collection introduced in the renewed National Cervical Screening Program. Methods : A total of 79 Aboriginal and/or Torres Strait Islander women (50 screened in previous five years, 29 under‐screened) from five clinics across three Australian states/territories participated. Topics discussed were perceptions of self‐collection, the instruction card and suggestions for implementing self‐collection. We employed yarning (a qualitative method), which established relationships and trust between participants and researchers to facilitate culturally safe conversations. Transcripts were analysed thematically. Results : Most women were unaware of self‐collection before the yarn but found it to be an acceptable way to participate in cervical screening. Women perceived self‐collection would be convenient, provide a sense of control over the screening experience, and maintain privacy and comfort. The instructions were perceived to be simple and easy to follow. Women had concerns about collecting the sample correctly and the accuracy of the sample (compared to clinician‐collected samples). Conclusions : Self‐collection is acceptable to Aboriginal and Torres Strait Islander women. Implications for public health : Given the inequitable burden of cervical cancer experienced by Aboriginal and Torres Strait Islander women, self‐collection is likely to significantly improve participation and ultimately improve cervical cancer outcomes.